2004
DOI: 10.1038/sj.ejhg.5201166
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin I-converting enzyme polymorphisms, ACE level and blood pressure among Nigerians, Jamaicans and African-Americans

Abstract: The genes in the renin -angiotensin system are important physiologic candidates in studies of the genetic susceptibility to hypertension. Limited information has been available in most studies on the extent of variation in the candidate loci or the modifying effects of different environmental settings. We consequently genotyped 13 polymorphisms at the angiotensin I-converting enzyme (ACE) locus at an average distance of 2 kb in 2776 family members from Nigeria, Jamaica and an African-American community in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 44 publications
3
24
0
1
Order By: Relevance
“…Haplotype data for three African [Nigerians, Afro-Americans, Jamaicans (Bouzekri et al 2004), and two Caucasian [British (Keavney et al 1998) and French (Villard et al 1996)] populations were collated. These haplotypes were collapsed to include the 9 polymorphic loci rs4277405, rs4459609, rs1800764, rs4291, rs4292(all regulatory), rs4309, rs4331, rs4343 (all exonic), and rs4340(intronic) to make the data comparable (Supplementary Materials & Methods We genotyped these nine loci ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Haplotype data for three African [Nigerians, Afro-Americans, Jamaicans (Bouzekri et al 2004), and two Caucasian [British (Keavney et al 1998) and French (Villard et al 1996)] populations were collated. These haplotypes were collapsed to include the 9 polymorphic loci rs4277405, rs4459609, rs1800764, rs4291, rs4292(all regulatory), rs4309, rs4331, rs4343 (all exonic), and rs4340(intronic) to make the data comparable (Supplementary Materials & Methods We genotyped these nine loci ( Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Their frequencies showed statistically significant differences (P \ 0.0001) across populations (Supplementary Table 2). In the African populations, three major haplotypes CCCTTCGIA (12-19%), TACATCADG (16-36%), and TACATCADA (25-29%) were present (Bouzekri et al 2004). The two major haplotypes in the non-African populations were TATATTGIA (38-72%) and CCCTCCADG (19-40%).…”
Section: Haplotype Distribution Among Africans and Non-africansmentioning
confidence: 99%
“…Linkage and segregation analysis have shown that circulating angiotensin-I converting enzyme (ACE) levels are infl uenced by a major quantitative (or continuous) trait locus that maps within the ACE gene [Bouzekri et al, 2004]. The ACE gene may be viewed as a candidate gene for (essential) hypertension.…”
Section: Nigerian Studymentioning
confidence: 99%
“…Data were available on 738 Nigerian individuals genotyped for 13 SNPs in a 26-kb region on the ACE gene. The thirteen polymorphic sites have been described elsewhere [Bouzekri et al, 2004] as ACE1-ACE5, ACEs12, ACEs11, ACE6, NewACE6, ACE7, I/D, ACE8 and ACE9, but we will refer to them as SNPs 1-13, respectively. These data are a subset of a larger study consisting of Jamaicans and African-Americans, that are less homogeneous because of admixture [Bouzekri et al, 2004].…”
Section: Nigerian Studymentioning
confidence: 99%
See 1 more Smart Citation